Very special episodes : televising industrial and social change - Cohn, Jonathan; Porst, Jennifer (Rutgers University Press, 2021)
Very Special Episodes examines how the quintessential "very special episode" format became a primary way in which the television industry responded to and shaped social change, cultural traumas, and industrial transformations. With essays covering shows ranging from the birth of Desi Arnaz, Jr. on I Love Lucy to contemporary examples such as a delayed episode of Black-ish and the streaming-era phenomenon of the "Very Special Seasons" of UnReal and 13 Reasons Why, this collection seriously and critically uses the "very special episode" to chart the history of American television and its self-identified status as an arbiter of culture